The Implications of Rahmatan Lil’Alamin in the Islamic Economics Context: A Study at an Islamic University in Indonesia - Adrian, Adrian; Junanah, Junanah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to examine the value of rahmatan lil'alamin at the Indonesian Islamic University in broadcasting Islamic economics. It focuses more on studying Indonesian Islamic universities. The method applied in this study is a literature study with a qualitative approach, a literature study whose data sources are obtained from written materials such as books or manuscripts, documents, and so on. The author will collaborate on various data from intellectual figures and continue a critique of the existing data by describing each piece of data found by the author. The author will try to separate what is considered right from what is wrong. The results of this study indicate that UII, as an educational institution in the midst of this society brings a paradigm of Islamic education rahmatan lil'alamin, which helps to think as a whole by studying in depth related to Islamic education, which is built through universal values based on the Qur'an and al-hadith, prioritizing love, togetherness, justice, and brotherhood towards fellow human beings, then in broadcasting the Islamic economy UII tries to collaborate with several Islamic financial institutions, companies and educational institutions both at home and abroad.